1978
DOI: 10.1073/pnas.75.9.4110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein synthesis initiation by oxidized glutathione: Activation of a protein kinase that phosphorylates the α subunit of eukaryotic initiation factor 2

Abstract: Oxidized glutathione (GSSG) (0.02-0.5 mM) inhibits reticulocyte lysates by a mechanism similar to that observed in heme deficiency. Incubation of hemin-supplemented postribosomal supernates with GSSG results in the activation of a translational inhibitor [I(GSSG)J. The activation of I(GSSG) is enhanced by the presence of an energy-regenerating system. The simultaneous addition of 1 mM dithiothreitol blocks the activation of the GSSG-induced inhibitor; however, once inhibitor is formed, its activity is not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…Dried moss regains more than 99% of its original fresh weight within 2 min of rehydration (RS Dhindsa, unpublished data) and the rapidly dried moss exhibits extensive membrane leakiness on rehydration (10, 1 1). The Studies of protein synthesis in rabbit reticulocyte lysate show that GSSG causes a rapid inhibition of the initiation step of protein synthesis (13,17) and that sugar phosphates and other NADPH-generating systems and thiol-reducing chemicals can reverse the GSSG-induced inhibition (15). In the present study, DTT did not stimulate protein synthesis, in contrast to the findings on rabbit reticulocyte lysate (15 (16).…”
Section: Resultscontrasting
confidence: 56%
“…Dried moss regains more than 99% of its original fresh weight within 2 min of rehydration (RS Dhindsa, unpublished data) and the rapidly dried moss exhibits extensive membrane leakiness on rehydration (10, 1 1). The Studies of protein synthesis in rabbit reticulocyte lysate show that GSSG causes a rapid inhibition of the initiation step of protein synthesis (13,17) and that sugar phosphates and other NADPH-generating systems and thiol-reducing chemicals can reverse the GSSG-induced inhibition (15). In the present study, DTT did not stimulate protein synthesis, in contrast to the findings on rabbit reticulocyte lysate (15 (16).…”
Section: Resultscontrasting
confidence: 56%
“…Changes in the redox state are known to influence the DNA-binding activity of several transcription factors, such as Oxy R (69), AP-1 (70), NF-κB (71), Egr-1 (72), Ets (73), Myb (74) and v-Rel. A redox mechanism is also known to contribute to cell cycle progression (76), hormone receptor interactions (77), bacteriophage DNA replication (78), light signal transduction (78,79), regulation of iron metabolism (80), protein-RNA and protein-DNA interactions and RNA transcription (81)(82)(83) and protein translation regulation (78,84). It is also known that ROS and H 2 O 2 can induce single-strand breaks in cellular DNA, oxidation of DNA bases, chromosomal aberrations and DNA-protein crosslinks (13,85,86).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of GSSG inhibition of in vitro protein synthesis in reticulocyte lysates has been the subject of several studies. It has been shown (11,12) that GSSG activates a translational inhibitor, a protein kinase, which phosphorylates and thereby inactivates the initiation factor eIF-2. It has been suggested that sugar phosphates, NADPH, and thiol-reducing systems are required to maintain a high rate of protein synthesis probably by keeping the inhibitor in the inactive state (13,14).…”
Section: Discussionmentioning
confidence: 99%